Perancangan Sistem Informasi Reservasi Lapangan Futsal Berbasis Web - Amirzan Sudrajat; Gunawan Gunawan (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to design a web-based futsal field reservation information system as a solution to the problems of the manual booking system, which often causes schedule conflicts, recording errors, and slow confirmation processes, resulting in less effective and efficient services. The method used in this research is the prototyping method, a system development method that directly involves users in the design process so that the resulting system meets user needs. The research stages include observation and interviews, analysis of functional and non-functional requirements, system modeling using the Unified Modeling Language (UML) in the form of use case diagrams, activity diagrams, sequence diagrams, and class diagrams, as well as system interface design using the Figma application, followed by evaluation to refine the system design. The result of this study is a web-based futsal field reservation information system design capable of displaying real-time schedules, automatically detecting booking schedule conflicts, simplifying the reservation process, and assisting administrators in managing field rental data. With this system, the reservation process becomes more structured, transparent, and efficient, and it has the potential to be developed further into a fully implemented system.